The Structure of the Local Interstellar Medium. VII. Additional New Mg ii, Fe ii, and Mn ii Observations toward Stars within 100 pc - Azmain H. Nisak; Seth Redfield; Jeffrey L. Linsky; Brian E. Wood; Allison Youngblood (The Astrophysical Journal)
We present new high-resolution ( R  ∼ 114,000), near-ultraviolet spectra in the direction of 36 nearby (<100 pc) stars to uncover the structure and composition of the local interstellar medium (LISM). The spectra were obtained using the Space Telescope Imaging Spectrograph on board the Hubble Space Telescope. We model the LISM absorption due to Mg ii , Fe ii , and Mn ii in order to measure new velocities, Doppler broadening parameters, and column densities for interstellar clouds; refine the extent of known clouds; and identify new clouds. Based on our analyses of these 36 new sight lines, we find one to four discrete LISM features for each individual sight line, with the number of components remaining relatively flat until increasing at  ≈60 pc. By comparing our final measurements with a dynamical model of the LISM by S. Redfield & J. L. Linsky, we determine that 77% of the predictions made by the kinematic model are confirmed by observed components in the new lines of sight and identify 10 LISM features among eight sight lines that do not match the model. In addition to testing and refining three-dimensional kinematic models of the LISM, the substantially increased number of integrated Mg ii emission fluxes presented here will be valuable for predicting the far-ultraviolet and extreme-ultraviolet emission for these stars. We also find that six stars in our sample show possible circumstellar disk absorption, including 47 UMa, for which a disk has not yet been confirmed.